Digital Holography and Three-Dimensional Imaging 2013
DOI: 10.1364/dh.2013.dm4a.4
|View full text |Cite
|
Sign up to set email alerts
|

Real time blood testing using quantitative phase imaging

Abstract: We demonstrate a real-time blood testing system that can provide remote diagnosis with minimal human intervention in economically challenged areas. Our instrument combines novel advances in label-free optical imaging with parallel computing. Specifically, we use quantitative phase imaging for extracting red blood cell morphology with nanoscale sensitivity and NVIDIA's CUDA programming language to perform real time cellular-level analysis. While the blood smear is translated through focus, our system is able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…Membrane fluctuation profiles showed that the mean membrane fluctuation levels decreased when the RBCs became spherocytes from the melittin treatment suggesting that melittin reduced the deformability of the RBCs. The measured values of the cell volume, surface area, sphericity, Hb concentration, dry mass, and mean fluctuation level of the control (0 nM) were in good agreement with previous results 30,[43][44][45][46] . The real-time measurements showed the characteristic time scale of the melittininduced changes and enabled us to study the Hb leakage process at high melittin concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Membrane fluctuation profiles showed that the mean membrane fluctuation levels decreased when the RBCs became spherocytes from the melittin treatment suggesting that melittin reduced the deformability of the RBCs. The measured values of the cell volume, surface area, sphericity, Hb concentration, dry mass, and mean fluctuation level of the control (0 nM) were in good agreement with previous results 30,[43][44][45][46] . The real-time measurements showed the characteristic time scale of the melittininduced changes and enabled us to study the Hb leakage process at high melittin concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…QPI can investigate unlabeled specimens, by converting optical pathlength data into biologically-relevant information [2][3][4][5][6][7][8][9][10]. Since the optical phase delay introduced by the specimen depends on both its thickness and refractive index, which essentially represents density, QPI has been used in a variety of applications, including topography and volume try of red blood cells [11,12], cell membrane fluctuations [13,14], cell growth [15,16], intracellular mass transport [17][18][19], cancer diagnosis in biopsies [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…More broadly viewed, the quantitative, label-free, and ease-of-use advantages of this method may have important clinical applications (37)(38)(39)(40)(41)(42), including characterizing the heterogeneous cell populations in human osteosarcoma tumors. Combined with clinical biomarker staining, one can envision that the percentages of angiogenic and non-angiogenic cells could be quantified using QPI, providing potentially useful information to pathologists as they evaluate the neovascularization of tumors being studied.…”
Section: Discussionmentioning
confidence: 99%